KOMUNIKASI PEMASARAN SOSIAL DALAM MERUBAH PERILAKUMASYARAKAT MENYIKAPI PENYAKIT LANGGANAN PADA ANAK - Masnah Masnah; Nieke Monika Kulsum (Universitas Nasional, 2015)
In developed countries, the pattern of health care has shifted, not overly paternalistic as in Indonesia. They had much to apply the concept of partnership or partnership between clinicians and consumers. On the other hand, in the communication era of health consumers have a goodunderstanding and proven health patients actively participate in addressing health problems, are important factors in creating a good climate of medical services. One of conducting social marketing in changing people's behavior to address high subscriptions disease in children, is the Foundation for Concerned Parents (YOP). Some of the concepts used in this study is theconcept of marketing communications, social marketing and consumer behavior. The approach of this research is descriptive qualitative. Data collection techniques were used: (1) in-depth interviews (2) nonpartisipatori observation, as well as exploring relevant data through books, websites, scientific journals, research reports, documents. From the overall results of the study, the outlines are social marketing communications management efforts undertaken by managers YOP using methods of marketing communications in order to change the behavior of health consumers. It is the most frequently performed activities of word of mouth and the internet (web, mailing lists, facebook, twitter, instant messenger) in an attempt to change the behavior of the middle class addressing subscriptions disease in children in Jakarta.